Digital Marketing sebagai Optimalisasi Pemasaran UMKM Produk Unggulan Masyarakat - Zuhdi, Rasyid; Waningyunq, Prissilia Prahesta; Sofyaningrum, Rosita; Prasetyo, Eko; Abror, Muchlas; Kurniawan, Muh Akbar; Azizah, Ririn Nurul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Digital marketing refers to promotional activities and market research conducted through online digital platforms, utilizing various tools such as social media. In today's interconnected world, the internet not only connects people to devices but also facilitates connections between individuals around the world. Small and medium enterprises (UMKM), in particular, are expected to drive economic growth in communities that have superior products in their region. By adopting Digital marketing strategies, UMKM can open up opportunities to grow and become major economic players. UMKM practitioners combine digital promotion and distribution channels to maximize profits. This approach is in line with the concept of utilizing technology to enhance marketing efforts, which ultimately benefits UMKM and allows them to thrive in the digital era.. Today, almost all small and medium-sized enterprises (UMKM), as well as restaurants and fast food businesses, rely heavily on Digital marketing for their promotion and distribution efforts. Interestingly, some businesses that initially relied on offline strategies have gradually regressed. Among the UMKM sector, the food industry is very popular and has become a means for the main income of the home industry in Kalibening Village, Kebumen Regency by utilizing the local superior product yam into various kinds of preparations. UMKM businesses continue to strive to survive by implementing various strategies, including increased promotion and offering ease of purchase. These efforts demonstrate optimization in the resilience of UMKM businesses.